2022
DOI: 10.3390/rs14205101
|View full text |Cite
|
Sign up to set email alerts
|

Using Tracking Data to Identify Gaps in Knowledge and Conservation of the Critically Endangered Siberian Crane (Leucogeranus leucogeranus)

Abstract: The critically endangered Siberian crane (Leucogeranus leucogeranus) is the world's third most endangered species of crane. Despite the enhanced conservation actions in recent years, there are pieces of evidence that suggest that its population is continuously decreasing. To gain insights into the possible causes of the population decline, we tracked nine Siberian cranes in Russia and Mongolia using GPS transmitters. We obtained migration episodes based on over 0.31 million subsequent locations from 3283 bird … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The duration of the autumn migration (49.6 ± 32.8) is longer than the duration of the spring migration (28.5 ± 22.4), which is consistent with the research conducted on the Western common crane in Europe [30,33]. Additionally, compared to other species of cranes, we found that the migration pattern of the Eastern common crane is most similar to that of the Siberian crane (Leucogeranus leucogeranus), which uses the same flyway in east Asia [28]. However, it is different from the migration pattern of White-naped cranes (Antigone vipio), which also migrate from Eastern Mongolia [34].…”
Section: Migration Patterns and Stopover Sites Of The Eastern Common ...supporting
confidence: 90%
See 1 more Smart Citation
“…The duration of the autumn migration (49.6 ± 32.8) is longer than the duration of the spring migration (28.5 ± 22.4), which is consistent with the research conducted on the Western common crane in Europe [30,33]. Additionally, compared to other species of cranes, we found that the migration pattern of the Eastern common crane is most similar to that of the Siberian crane (Leucogeranus leucogeranus), which uses the same flyway in east Asia [28]. However, it is different from the migration pattern of White-naped cranes (Antigone vipio), which also migrate from Eastern Mongolia [34].…”
Section: Migration Patterns and Stopover Sites Of The Eastern Common ...supporting
confidence: 90%
“…Stopover sites were identified as places where birds remained stationary during the migration for more than two days [25]. Sites where the cranes stayed for more than 14 days were determined to be "critical stopover sites" [27,28].…”
Section: Migration Analysismentioning
confidence: 99%
“…Similarly, there is a growing interest in estimating underlying, or latent, behavioral states based on movement quantities related to locations of an individual through time, typically referred to in the movement literature as hidden Markov-models (McClintock et al 2012). These advances in data collection and analysis have increased our understanding of the ecology and evolution of migratory behavior (Mueller et al 2013; Gu et al 2021), conservation of at risk species and populations (Liang et al 2023), connectivity of migratory populations (Alheit and Bakun 2009; Kot et al 2022), optimal habitats to prioritize for conservation (Yi et al 2022), movement of pathogens (Takekawa et al 2023), and ways in which species respond to climate change (Youngflesh et al 2021; Horton et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Among migratory birds, cranes have been widely studied using satellite telemetry across most of their range [12][13][14][15][16]. However, in India, the use of satellite telemetry to study birds is limited.…”
Section: Introductionmentioning
confidence: 99%